Inductive‐dynamic magnetosphere‐ionosphere coupling via MHD waves. Issue 1 (23rd January 2014) - Tu, Jiannan; Song, Paul; Vasyliūnas, Vytenis M.
<x xml:space="preserve">Abstract</x> In the present study, we investigate magnetosphere‐ionosphere/thermosphere (M‐IT) coupling via MHD waves by numerically solving time‐dependent continuity, momentum, and energy equations for ions and neutrals, together with Maxwell's equations (Ampère's and Faraday's laws) and with photochemistry included. This inductive‐dynamic approach we use is fundamentally different from those in previous magnetosphere‐ionosphere (M‐I) coupling models: all MHD wave modes are retained, and energy and momentum exchange between waves and plasma are incorporated into the governing equations, allowing a self‐consistent examination of dynamic M‐I coupling. Simulations, using an implicit numerical scheme, of the 1‐D ionosphere/thermosphere system responding to an imposed convection velocity at the top boundary are presented to show how magnetosphere and ionosphere are coupled through Alfvén waves during the transient stage when the IT system changes from one quasi steady state to another. Wave reflection from the low‐altitude ionosphere plays an essential role, causing overshoots and oscillations of ionospheric perturbations, and the dynamical Hall effect is an inherent aspect of the M‐I coupling. The simulations demonstrate that the ionosphere/thermosphere responds to magnetospheric driving forces as a damped oscillator.